2012
DOI: 10.1016/j.jtcvs.2012.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous aortic valve implantation using the axillary/subclavian access with patent left internal thoracic artery to left anterior descending artery: Feasibility and early clinical outcomes

Abstract: This initial experience suggests that subclavian transarterial aortic valve implantation in patients with a patent left internal thoracic artery to left anterior descending artery is feasible and safe with satisfactory short-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…However, this access carries a certain risk in patients with LIMA (or RIMA in case of right sided access) grafts or previously implanted ipsilateral pacemakers . Also, the subclavian artery is located deep inside the thorax which complicates access control, and damage of the brachial plexus is a potential side effect . Our patient had severe peripheral artery disease, a patent aorto‐bi‐iliac bypass graft, a LIMA‐LAD anastomosis and an unfavorable and diseased innominate artery that rendered the femoral and subclavian/transaxillary routes unsuitable.…”
Section: Discussionmentioning
confidence: 92%
“…However, this access carries a certain risk in patients with LIMA (or RIMA in case of right sided access) grafts or previously implanted ipsilateral pacemakers . Also, the subclavian artery is located deep inside the thorax which complicates access control, and damage of the brachial plexus is a potential side effect . Our patient had severe peripheral artery disease, a patent aorto‐bi‐iliac bypass graft, a LIMA‐LAD anastomosis and an unfavorable and diseased innominate artery that rendered the femoral and subclavian/transaxillary routes unsuitable.…”
Section: Discussionmentioning
confidence: 92%
“…For patients with previous sternotomy, transaortic access is hazardous. Other modes of vascular access, (particularly axillary artery cut‐down) have been reported [] for implantation of the Medtronic CoreValve device. The axillary artery cutdown route, however, is often limited by vessel size or angulation, disease of the proximal vessel, or the presence of a functionally important internal mammary artery bypass.…”
Section: Discussionmentioning
confidence: 99%
“…In this subgroup of patients, besides all potential complications listed above, the presence of a patent LIMA‐LAD graft represents an additional risk for direct axillarian artery cannulation. Initial reports demonstrated that this could be feasible when the vessel diameter is large enough to accommodate the sheath without occluding the ostium of the graft or when the sheath is not advanced across the LIMA origin . The use of the bareback “chimney” side graft technique allowed, in our experience, to maintain an adequate flow through the LIMA‐LAD avoiding extensive manipulation of the vessel wall that could potentially cause dissection or occlusion.…”
Section: Discussionmentioning
confidence: 82%